Virus in infectious uveitis: bibliometric analysis and a clinical study - Shen, Junhui; Kong, Jinfeng; Xu, Yufeng; Hu, Yanyan; Feng, Lei (Frontiers in Microbiology, 2025)
IntroductionIn recent years, advancements in detection technology have led to increased research interest in viral uveitis.MethodsThis study conducted a comprehensive analysis, comprising a bibliometric examination of literature on virus and infectious uveitis and a retrospective study focusing on infectious uveitis. The bibliometric analysis aimed to elucidate past and emerging trends in this field over several decades. In the retrospective study, intraocular fluid samples were collected from 73 patients suspected of having infectious uveitis for metagenomic next-generation sequencing (mNGS), with 29 samples also subjected to microbiological culture.ResultsAnalysis of the literature revealed a steady rise in annual publications on virus and infectious uveitis from 1990 to 2021, reaching a peak in 2021. The United States emerged as the most prolific contributor, with significant collaborative relationships with other nations. Keywords were clustered into five categories, covering diagnostic criteria, diagnostic tools, clinical manifestations, epidemiology, and etiology of viral uveitis. Interestingly, research focus shifted from predominant viral types and serodiagnosis towards intraocular fluid testing. mNGS demonstrated a notably higher positivity rate (73.97%) compared to culture (3.45%), identifying various pathogens including viruses, bacteria, fungi, Toxoplasma gondii, and Rickettsia felis. Varicella-Zoster Virus, Epstein–Barr Virus, Klebsiella pneumoniae, and Torque Teno Virus were among the most common pathogens detected. Additionally, coexisting microorganisms such as Torque Teno Virus and Epstein–Barr Virus were identified.ConclusionViral uveitis has consistently garnered research attention, with future directions likely focusing on virus types and diagnostic tools. Viruses are the main causative microorganisms of infectious uveitis. The high efficacy of mNGS in identifying diverse pathogens from minute volumes of intraocular fluid samples highlights its pivotal role in diagnosing infectious uveitis.